15N2 as a tracer of biological N2 fixation: A 75-year retrospective. (March 2017) - Chalk, Phillip M.; He, Ji-Zheng; Peoples, Mark B.; Chen, Deli
Abstract: 15 N2 has played a crucial role in fundamental studies of biological N2 fixation. However, due to operational constraints, it has more often served as a qualitative rather than a quantitative tracer of biologically-fixed N (BFN). Therefore indirect methods based either on 15 N-enrichment or 15 N-natural abundance have assumed a dominant role in quantifying N cycle processes involving BFN. However, it is only through the direct 15 N2 approach that biological N2 fixation can be traced through the various components of the soil-plant system. Technological advances in the automated control of the chamber environment have made the 15 N2 technique more attractive to long-term studies. Thus the need to enclose plants in a chamber and maintain conditions conducive to plant growth should no longer be seen as a major obstacle to the use of 15 N2 . The way is now open to evaluate the efficacy of indirect methods used to estimate the contribution of BFN to the N economies of crop and pasture systems, and the dynamics of BFN in agroecosystems. In addition, new applications of 15 N2 such as stable isotope probing are emerging, which have the potential to characterize non-cultivated diazotrophs in a range of environments. The role of biological N2 fixation in the formation of reactive N in the environment and its relationship with the emission of the greenhouse gas N2 O requires further investigation. Highlights: 15 N2 is the only direct method for quantifying biological N2 fixation (BNF). The central role of 15 N2 in studies of BNF over the past 75 years is reviewed. Indirect 15 N methods for estimating BNF should be verified by the 15 N2 method. Stable isotope probing with 15 N2 can identify uncultured diazotrophs. The role of BNF as a source of reactive N and N2 O requires further study.